Understanding and communicating research results in English in full-time and part-time course modalities (in the times of COVID-19) - Adrian Abreus González; Norma Mur Villar; Miriam Iglesias León (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Background: the doctoral training of the cloister belonging to the University of Medical Sciences of Cienfuegos is a fundamental task, for which a set of actions has been developed that contribute to the fulfillment of the stages and processes that underlie this type of postgraduate training. Objective: to train candidate Doctor of Sciences in the development of skills in the English language at an advanced level that allows them to analyze, understand and communicate the results of science in their areas of scientific performance. Methods: the contents of a postgraduate course taught to candidates enrolled in the doctoral training strategy of the Cienfuegos Medical Sciences University were put into practice, both face-to-face and non-face-to-face modalities of the COVID-19 pandemic and the results obtained in the development of defined English language skills were described. Results: significant advances are shown in the development of translations into Spanish of scientific articles in English, as well as the communication and understanding of scientific information in that language, orally and in writing. These results are analyzed from the perspective of face-to-face and non-face-to-face modalities in times of COVID-19, establishing similarities and differences in the skills development process. Conclusions: both in the face-to-face and non-face-to-face modes, doctoral students obtain satisfactory results in their preparation process in foreign languages, especially from direct and systematic exchange with the teacher and among themselves.